A Case Study in Supporting a Child with ADHD Experiencing Trauma and Adaptive Problems at School (Sains Humanika, 2025)
Neurodevelopmental disorders, such as attention deficit hyperactivity disorder (ADHD), have been increasingly recognized in Japan in recent years. However, support for families who have migrated to Japan remains limited. The aim of this case study was to examine (1) the effectiveness of play therapy and family therapy for a child with a neurodevelopmental disorder who experienced trauma due to domestic violence, and (2) the role of the therapist as a facilitator in promoting collaboration among professionals supporting the child. Play therapy was conducted weekly over a 24-month period, while psychoeducation and family therapy were provided to the parents on a monthly basis. Additionally, the therapist implemented strategies to improve the family and school systems, and acted as a liaison to bridge communication gaps between the parents, doctor, teacher, and child services staff. Results demonstrated a significant reduction in the father’s tendency toward domestic violence and marked improvements in the child’s ability to communicate freely at home. Furthermore, the therapist’s role as a liaison successfully improved communication among professionals, although challenges remained in establishing effective coordination within the school system. These findings highlight the importance of play therapy in helping children express their experiences and the value of addressing family communication patterns and narratives. They also underscore the critical role of the therapist in fostering interprofessional collaboration to provide comprehensive support for children with trauma.
Keywords: Neurodevelopmental disorder, trauma, play therapy, family therapy